Schizasterid Heart Urchins Host Microorganisms in a Digestive Symbiosis of Mesozoic Origin - Ziegler, Alexander; Gilligan, Ariel M.; Dillon, Jesse G.; Pernet, Bruno (Frontiers in Microbiology, 2020)
Because of their lifestyles, abundance, and feeding habits, infaunal marine deposit feeders have a significant impact on the ocean floor. As these animals also ingest microorganisms associated with their sediment and seawater diet, their digestive tract usually contains a diverse array of bacteria. However, while most of these microorganisms are transients, some may become part of a resident gut microbiome, in particular when sheltered from the main flow of digesta in specialized gut compartments. Here, we provide an in-depth analysis of the structure and contents of the intestinal caecum (IC), a hindgut diverticulum found exclusively in schizasterid heart urchins (Echinoidea: Spatangoida: Schizasteridae). Based on specimens of Brisaster townsendi, in addition to various other schizasterid taxa, our structural characterization of the IC shows that the organ is a highly specialized gut compartment with unique structural properties. Next generation sequencing shows that the IC contains a microbial population composed predominantly of Bacteroidetes, Desulfobacterales, and Spirochaetales. The microbiome of this gut compartment is significantly different in composition and lower in diversity than the microbial population in the sediment-filled main digestive tract. Inferences on the function and evolution of the IC and its microbiome suggest that this symbiosis plays a distinct role in host nutrition and that it evolved at least 66 million years ago in the final phase of the Mesozoic.